Enhancing the Performance of Medical Teams through Recruitment and Selection Processes - Iin Novita Evan; Agung Surya Dwianto (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to analyse the recruitment and selection process on project employee performance in the nurse function at Klinik Pertamedika IHC. This research will focus on evaluating the effectiveness of the current recruitment and selection process in identifying and hiring qualified project employees. The research will also examine the impact of these processes on the performance of project employees in the nursing function. This research will utilise a qualitative method approach. The research will involve in-depth interviews with key stakeholders and analysis of performance data. This study adopts a qualitative research approach with a descriptive nature. It focuses on the recruitment and selection process of employees and their impact on performance within Klinik Pertamedika IHC. The research was conducted at Klinik Pertamedika IHC from February to May 2023, and the data collection process involved both offline and online interviews. The findings from this research will provide insights into the effectiveness of the recruitment and selection process in the nursing function and inform recommendations for improving this process to enhance project employee performance.